Karakteristik Turbin Archimedes pada Ketinggian Air Rendah dan Kemiringan 45° - Ikhsan, Ghufra; Fernanda, Yolli; Karudin, Arwizet; Primawati, Primawati (TSAQOFAH, 2025)
Turbines are a key component in hydroelectric power generation, including the Archimedes Screw type, which is specifically designed to operate under low head and low water discharge conditions. This study aims to calculate the rotational speed of the Archimedes Screw turbine under varying water discharge rates, analyze the effect of discharge on turbine rotation, and compute and evaluate the turbine’s efficiency. A quantitative experimental approach was employed, with data obtained through direct testing of a designed Archimedes Screw turbine prototype. Research instruments included measurements of turbine rotational speed and the generated electrical power. Tests were conducted three times at a 45° inclination angle. The results showed that the actual power (Pactual) generated was 11.95 Watts in the first trial, 10.96 Watts in the second, and 12.56 Watts in the third. These findings indicate variations in power output influenced by water discharge and demonstrate the potential of the Archimedes Screw turbine as a micro-hydro energy solution for low-flow water sources. The study concludes that optimizing design and operational parameters is essential for improving the efficiency of such power generation systems.